Current Outcomes of Laparoscopic Duodenal Switch - Biertho, Laurent (Ann Surg Innov Res, 2016)
BACKGROUND: Biliopancreatic diversion with duodenal switch (BPD-DS) has long been considered as the bariatric procedure with the highest peri-operative and long-term complication rate. However, modern peri-operative care, including laparoscopic and staged-approach, has significantly reduced the complication rate related to this procedure. The goal of this article is to provide an overview of the current outcomes of laparoscopic BPD-DS in a high volume centre. METHODS: All patients who had a laparoscopic BPD-DS with a hand-sewn anastomosis performed between 2011 and 2015 (N = 566) were reviewed. Data were obtained from our prospectively maintained electronic database and are reported as a Mean ± standard deviation. RESULTS: The mean age of the 566 patients was 41 ± 10 years, with 78 % women. Initial body mass index was 49 ± 6 kg/m(2). There was no 90-days mortality. Hospital stay was 4.5 ± 3 days. Major 30-days complications occurred in 3.0 % (n = 17) of the patients and minor complications in 2.5 % (N = 14). Excess weight loss was 81 ± 14 % at 12 m, 88 ± 13 % at 24 m, 83 ± 14 % at 36 months. Total body weight loss (kg) was 57 ± 13 kg at 12 months, 63 ± 14 kg at 24 months and 61 ± 17 kg at 36 months. Hemoglobin A1C (HbA1C) dropped from 6.1 ± 1 % to 4.7 ± 0.5 % (p < 0.005) and the percentage of patients with an HbA1C above 6 % decreased from 38 to 1.4 % (p < 0.005). Over 21 ± 12 months follow-up, readmission was required in 3.5 % and reoperation in 0.5 % of the patients. CONCLUSION: The current short and medium-term complication rate of laparoscopic BPD-DS are similar to other mixed bariatric procedures with excellent metabolic outcomes.